2017
DOI: 10.1038/s41598-017-04288-2
|View full text |Cite
|
Sign up to set email alerts
|

Two alternative pathways for docosahexaenoic acid (DHA, 22:6n-3) biosynthesis are widespread among teleost fish

Abstract: Docosahexaenoic acid (DHA) plays important physiological roles in vertebrates. Studies in rats and rainbow trout confirmed that DHA biosynthesis proceeds through the so-called “Sprecher pathway”, a biosynthetic process requiring a Δ6 desaturation of 24:5n−3 to 24:6n−3. Alternatively, some teleosts possess fatty acyl desaturases 2 (Fads2) that enable them to biosynthesis DHA through a more direct route termed the “Δ4 pathway”. In order to elucidate the prevalence of both pathways among teleosts, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 57 publications
6
120
0
Order By: Relevance
“…Unlike Elovl5 though, the tambaqui Elovl2 had efficiency to operate towards C22 substrates. For instance, 22:5n-3 was efficiently elongated to 24:5n-3, a key intermediate component of the so-called "Sprecher pathway", a metabolic route that accounts for DHA biosynthesis in vertebrates (Buzzi et al, 1996(Buzzi et al, , 1997Sprecher, 2000) and recently demonstrated to be widespread among teleosts (Oboh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike Elovl5 though, the tambaqui Elovl2 had efficiency to operate towards C22 substrates. For instance, 22:5n-3 was efficiently elongated to 24:5n-3, a key intermediate component of the so-called "Sprecher pathway", a metabolic route that accounts for DHA biosynthesis in vertebrates (Buzzi et al, 1996(Buzzi et al, , 1997Sprecher, 2000) and recently demonstrated to be widespread among teleosts (Oboh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Yeast were transformed with the C. macropomum fads2 ORF and grown in the presence of Δ6 (18:2n-6 and 18:3n-3), Δ8 (20:2n-6 and 20:3n-3), Δ5 (20:3n-6 and 20:4n-3), and Δ4 (22:4n-6 and 22:5n-3) fatty acid (FA) substrates. Desaturation of 24:5n-3 was tested by co-expressing both D. rerio elovl2 and C. macropomum fads2 in S. cerevisiae (Oboh et al, 2017) Expressed with D. rerio elovl2 18:3n-3 18:4n-3 20.5 Δ6 24:5n-3 24:6n-3 21.9 Δ6 a Conversions of Δ8 substrates (20:2n-6 and 20:3n-3) include stepwise reactions due to multifunctional desaturation abilities. Thus, the conversions of the C. macropomum Fads2 on 20:2n-6 and 20:3n-3 include the Δ8 desaturation toward 20:3n-6 and 20:4n-3, respectively, and their subsequent Δ5 desaturations to 20:4n-6 and 20:5n-3, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CCA biplots of total lipids, PL and TAG, charr had a particular position due to higher levels of minor n-3 PUFA, like 22:4-3, C24 PUFA and 20:3n-3. These FA were not assigned as trophic markers, whereas some of them, C24 PUFA, were considered as intermediate compounds indicative for conversion of C20 to C22 PUFA [34,35]. In TAG of charr the percentage of 22:4n-3 accounted for 1.3% of FA sum, being absent or found in traces in other studied fish.…”
Section: Fatty Acid Markers In Fish Total Lipids Tag and Plmentioning
confidence: 99%
“…As for Fads2, majority of the Teleostei groups not only retain the Δ6 capacity but undergo functionalisation for Δ4, Δ5 and Δ8 desaturation capabilities (Zheng et al, 2004, Zheng et al, 2009a, Tanomman et al, 2013, Fonseca-Madrigal et al, 2014). Many of the characterised Fads2 sequences also have bifunctional desaturation activities (Monroig et al, 2011, Kabeya et al, 2015, Oboh et al, 2017). The Fads from the four mudskipper species shares a common ancestor with Fads2 of various percomorpha fishes.…”
Section: Discussionmentioning
confidence: 99%